Analyzing the Composite Effect of Corruption and Socio-Economic Variables on Food Insecurity in Pakistan: A Comprehensive Study - Saira Habib; Hasnain Didar (Население и экономика)
Food insecurity affects 842 million people, or 12% of the global population, with Asia and Africa accounting for over 92% of the undernourished population. Notably, South Asia comprises 35% of this figure. In countries like Pakistan, factors such as corruption, foreign investment, remittances, education, population growth, gross domestic product (GDP), and unemployment exacerbate food insecurity. This study, based on data from the World Development Indicators (WDI) and Transparency International spanning 1995 to 2021, employs an Autoregressive Distributed Lag (ARDL) Model to examine both short- and long-term relationships between corruption and socio-economic variables. Our findings reveal that corruption, population growth, and unemployment significantly increase food insecurity. Specifically, corruption negatively impacts production and quality management, while high unemployment discourages production, and population growth strains available resources. Conversely, GDP growth is found to significantly reduce food insecurity, suggesting that economic growth can help address this issue. Additionally, education, remittances, and foreign direct investment pose potential threats to food security. For Pakistan’s long-term economic development, reducing food insecurity is essential, underscoring the need for political stability. Effective oversight of corruption, and strategic management of GDP, inflation, and remittances are vital to stabilizing food security.